REDUCTION OF THE QUANTITY OF DEGRADATION BY DETERMINING THE OPTIMUM LOCATION OF MINING LAYER Н2Б SOLDER IN “DEHKONABAD POTASSIUM PLANT” JSC TEPAQOTON MINING COMPLEX - Gaibnazarov, S.B.; Ismailov, A.S.; Maxmudov, Dilmurod; Khujakulov, Amirjon; Olimov, Farusxon (Sanoatda raqamli texnologiyalar, 2023)
In this article, the causes of spoilage and deterioration of mineral extracted from Tepaqoton mining complex are systematically analyzed and the main causes of spoilage and deterioration are identified. In addition, reasonable proposals for reducing degradation and failure have been developed. The optimal location of the working in layers was determined and the parameters for reducing losses were determined.